LINGKUNGAN KAMPUNG BERKELANJUTAN DAN POTENSI MASYARAKAT DI KAMPUNG KANALSARI, SEMARANG, INDONESIA. (Studi Kasus: Kampung Kanalsari – Semarang) - Widiastuti Sari; Yuliastuti Nany (Diponegoro University, 2012)
Low-income communities tend to live in the urban village areas (defined as ’kampong’), which presence isprevalent in several major cities in Indonesia. Kampong is a neighborhood or residential area of low-incomepeople with poor physical conditions. Kampong is a traditional neighborhood which is marked by the features ofclose-knit relationships (Herbasuki, 1984). The legitimate land ownership motivates the people to build anddevelop houses and neighborhoods, in accordance with the economic ability of the family. Housinginfrastructure development that is generally taking place in the Indonesian kampongs are commonly carried outby the kampongs’ residents together with the municipal government. This has been the common practice in orderto sustain and prevail the existence of the kampongs.This paper is the result of a study on the effects of infrastructure development that are viewed from theperspectives of physical conditions of the kampong as well as the socio-economic conditions of the communitiesin Kampong Kanalsari, Semarang, Indonesia. With the use of a mixed-methods approach coupled with aquantitative analysis, the outcomes of study are as follows: 1) residents of kampongs evidently have highmotivation to prioritize on the development of infrastructure; 2) there is a high level of social quality, whichproves that the character of the people who have harmonious society have and still survive in KampungKanalsari; 3) the development and improvement of village infrastructure that are conducted independently andby non-government institutions positively impacts the physical conditions of the housing environments, socialand economic conditions of the community. The influence of social conditions occupies the highest level becausethe development is carried out independently, based on the aspirations, interests and needs of the community,which ultimately provide benefits and advantages for the kampong’s residents. This influence would directlyaffects the community as it increases their motivation to build and improve the housing conditions andenvironmental sustainability in order to ensure security and liveability of the residential area.